2021
DOI: 10.1029/2020jb021388
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Symmetry in the Lithospheric Structure of the Alboran and Algerian Basins and Their Margins (Western Mediterranean): Geodynamic Implications

Abstract:  Oppositely symmetric lithosphere and upper mantle structure is observed in the Alboran & Algerian basins, & their margins with subduction related HP/LT rocks.  Subducted Ligurian-Tethys slabs beneath the Betics & Kabylies are ~400 o C colder & at least ~30 kg/m3 denser than upper mantle.  Eastern Betics & Greater Kabylies underwent mantle delamination during Middle-Late Miocene and further slab break-off triggered by slab retreat of the subducted Ligurian-Tethys segments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 170 publications
(418 reference statements)
1
20
0
Order By: Relevance
“…Seismic velocities are calculated based on phase and mineral assemblages and on the obtained temperature and pressure conditions and are compared with available velocity and tomography models. LitMod2D approach has been successfully applied in different tectonic settings including continental margins (e.g., Fernàndez et al, 2010;Pedreira et al, 2015) and continental collisional regions (e.g., Carballo et al, 2015;Jiménez-Munt et al, 2019;Kumar et al, 2021;Tunini et al, 2015). For more details about LitMod2D the reader is referred to Afonso et al (2008) and Kumar et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic velocities are calculated based on phase and mineral assemblages and on the obtained temperature and pressure conditions and are compared with available velocity and tomography models. LitMod2D approach has been successfully applied in different tectonic settings including continental margins (e.g., Fernàndez et al, 2010;Pedreira et al, 2015) and continental collisional regions (e.g., Carballo et al, 2015;Jiménez-Munt et al, 2019;Kumar et al, 2021;Tunini et al, 2015). For more details about LitMod2D the reader is referred to Afonso et al (2008) and Kumar et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…(2020). A similar approach has been used to study the deep structure of the Gibraltar Arc region (Jiménez‐Munt et al., 2019) and along the Algerian and Alboran basins of the Western Mediterranean (Kumar et al., 2021). Both studies demonstrated that the pull force of hanging lithospheric slabs is markedly different if the slab is still attached to the continental lithosphere or is detached after break‐off processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Algero-Balearic basin shows a more complex evolution, presenting segments of different ages, as made manifest by the heat flow and magnetic anomaly distribution, suggesting younger oceanic crust located at the western and eastern ends of the basin (Haidar et al, 2021;Poort et al, 2020). Moreover, the Algero-Balearic basin is underlain by at least two different Tethyan slab segments, underneath the Betics-Rif and Algerian-Tunisian orogenic arcs (e.g., Faccenna et al, 2014;Fichtner & Villaseñor, 2015;Kumar et al, 2020;van Hinsbergen et al, 2014). The westernmost segment of the Algero-Balearic basin formed behind the Alboran volcanic arc in the Eastern Alboran basin during the Middle to Late Miocene (Booth-Rea et al, 2007, Booth-Rea, Ranero, & Grevemeyer, 2018de la Peña, Ranero, et al, 2020;Duggen et al, 2004Duggen et al, , 2008.…”
Section: Geodynamic Settingmentioning
confidence: 99%
“…These lithospheric movements have amplitudes of hundreds of meters and have controlled the thermal as well as subsidence history and source rocks maturity of the basins and preservation/ migration of oil and gas in traps and reservoirs. A recent study of the lithospheric structure of the Tunisian margin determined that the combined processes of delamination and slab break-off could affect a region with a wavelength of 100 km reaching dynamic topographies of ≥ 500 m (Kumar et al, 2021).…”
Section: Northern Africa Tell and Atlas Fold And Thrust Belts In Thei...mentioning
confidence: 99%